CULTURAL NATIONALISM AND THE IRISH LITERARY REVIVAL - Pierce, David (International Journal of English Studies, 2002)
The impact of cultural nationalism on the Insh Literary Revival is a topic of continuing interest for the cultural critic and literary historian alike. In recent years, with the Fa11 of the Berlin Wall, political scientists and others, suchas A.D. Smith, Ernest Gellner, and E.J. Hobsbawm, have also focused on the subject of nationalism. The intention here in this article is to revisit a familiar site in the light of these new ideas and to test their validity or appropriateness in the Irish context. The article, part of a larger project to be published in 2003 by Polity Press under the title A Cultural History of Twentieth-Century Irish Literature, is divided into 5 sections: What ish my Nation?; What is a Nation?; Do Nations Have Navels?; 1890s: Winds of Change; English As We Speak It In Ireland. Among Irish authors discussed are Hyde, Shaw. Yeats, Wilde, Lady Gregory, Joyce, and Beckett.